2011
DOI: 10.1159/000328778
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Gene-Environment Interactions before 1 Year of Age May Favor the Development of Atopic Dermatitis

Abstract: Background: The aims of this study were to determine (1) the prevalence of atopic dermatitis (AD) in Seoul, Korea, and (2) the influence of environmental and genetic factors on disease risk. Methods: A questionnaire survey was conducted in 5,036 primary school children and 4,607 middle school children in 2008. For each child, a modified version of the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire and a questionnaire assessing exposure to environmental variables were completed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 68 publications
2
47
2
1
Order By: Relevance
“…4,8,16,30) In the present study, parental history of AD was the only significant familial risk factor for AD in preschool children; parental histories of other allergic diseases such as asthma and allergic rhinitis were not significant.…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…4,8,16,30) In the present study, parental history of AD was the only significant familial risk factor for AD in preschool children; parental histories of other allergic diseases such as asthma and allergic rhinitis were not significant.…”
Section: Discussioncontrasting
confidence: 45%
“…16) Previously we reported early life exposure to mold was important risk factor for the development of AD especially in susceptible children. 4) Some studies have shown that markers of indoor dampness, such as visible mold and water damage, were associated with increased risk of AD in childhood, 17,18) but this association was not found in all studies. 6) The relative importance of mold exposure for the development of AD in preschool children remains unexplored.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations